Intuition in judgment and decision making: [conference on "Intuition in Judgment and Decision Making" held at the University of Heidelberg, Germany, in 2004] - Plessner, Henning; Betsch, Cornelia; Betsch, Tilmann (Erlbaum, 2008)
The nature of intuition -- Learning and intuition -- Emotion and intuition -- The assets and deficits of intuition
Includes bibliographical references and index. - Partly based on a conference held at the University og Heidelberg, Germany, in 2004
Keywords: Konferenzschrift; Entscheidungsfindung; Intuition